Joint entropy analysis of anterior-posterior and medial-lateral body sway. (August 2022) - Anagnostou, Evangelos; Karagianni, Evangelia; Skoularidou, Maria
Highlights: Sway entropy provides new information not captured by conventional linear metrics. Postural sway complexity appears invariant to task difficulty. Medial-lateral and anterior-posterior sway entropies are close to randomness. Joint sway entropy exhibits reduced disorder as compared to individual entropies. Abstract: We studied the Shannon entropy of center of pressure (COP) trajectories under different sensory feedback conditions and analyzed the interrelations between medial-lateral (ML), anterior-posterior (AP) and joint (ML and AP) sway entropy. Static balance was assessed on a force platform under different visual and proprioceptive feedback conditions: Standing on firm support with eyes open (condition 1) or closed (condition 2) and standing on foam with eyes closed (condition 3). Postural sway was analyzed by means of linear and nonlinear, information theoretic metrics (entropy of ML and AP sway, joint ML and AP entropy). ML entropy, AP entropy and joint ML and AP entropy remained stable from condition 1 through condition 3. The values of ML and AP entropies were practically at their theoretical maximum in all conditions. On the other hand, joint ML and AP entropies were clearly submaximal. Decreasing the reliability of visual and proprioceptive input does not alter the Shannon entropy of body sway, although it does increase the magnitude of conventional linear sway metrics. Importantly, individual ML and AP sway entropies tend towards absolute randomness, whereas the joint, ML and AP, sway entropy exhibits a higher degree of regularity, suggesting its role as the actual controlled variable.